Laparoscopic Adjustable Gastric Banding and Hypoglycemia - Sigrid Bairdain; Mark Cleary; Chueh Lien; Ashley H. Vernon; Bradley C. Linden; David B. Lautz (Case Reports in Endocrinology)
Obesity is commonplace, and surgical treatment usually includes Roux-en-Y gastric bypasses (RYGBs). RYGBs have the most documented side effects including vitamin deficiencies, rebound weight gain, and symptomatic hypoglycemia; fewer series exist describing hypoglycemia following other bariatric operations. We reviewed all patients undergoing laparoscopic adjustable gastric banding (LAGB) at our institution between 2008 and 2012. Three patients were identified to have symptomatic hypoglycemia following LAGB. Mean time from surgery was 33 months (range 14–45 months), and mean weight loss was 32.7 kg (range 15.9–43.1 kg). None of the patients had preexisting diabetes. Therefore, symptomatic hypoglycemia should be investigated irrespective of bariatric operation.